REPRODUCTION AND ITS REGIONAL DIFFERENCES IN THE REPUBLIC OF UZBEKISTAN - Tojieva, Z.N.; Dusmanov, F.А. (International Journal of Psychosocial Rehabilitation, 2020)
This article reveals the process of reproduction, its factors of influencing and the regionalization. Also there is given data and facts about demographic flow of the world population and the brief information about demographic revolution and present conditions of depopulation. Moreover, this article also provides brief information regarding to the giving birth in the administrative-territorial units of the Republic of Uzbekistan, reproduction processes and their causes and effects.